Left atrial enlargement and high uric acid level are risk factors for left atrial thrombus or dense spontaneous echo contrast in atrial fibrillation patients with low to moderate embolic risk assessed by CHA2DS2-VASC score - Tan, Chao-Di; Liu, Juan-Zhang; Zheng, Yu-Ping; Li, Zong-jian; Zhou, Shu-Xian (Frontiers in Cardiovascular Medicine, 2023)
Aims To investigate the correlation and predictive value of left atrial diameter and blood uric acid levels with the occurrence of left atrial thrombus or dense spontaneous echo contrast in atrial fibrillation patients with low to moderate CHA2DS2-VASc scores. Methods and results A total of 849 inpatients diagnosed with atrial fibrillation who had low to moderate CHA2DS2-VASc scores and complete transesophageal echocardiography were included in this study. Among them, 66 patients had left atrial thrombus or dense spontaneous echo contrast. When different models were used to correct other known risk factors, acid levels and abnormal left atrial diameter were identified as additional risk factors for left atrial thrombus or dense spontaneous echo contrast. The incidence of left atrial thrombus or dense spontaneous echo contrast was higher in patients with abnormal serum uric acid levels than in the control group (12.4% vs. 5.6%, p < 0.05), and this difference persisted after correcting the baseline data with propensity score matching (10.6% vs. 4.1%, p < 0.05). Abnormal left atrial diameter was another risk factor suggested by regression analysis, with an increased incidence of left atrial thrombus or dense spontaneous echo contrast in the abnormal left atrial diameter group compared to the control group, both before (18.0% vs. 3.5%, p < 0.05) and after (15.5% vs. 5.2%, p < 0.05) propensity score matching. The best predictive value was obtained by adding both abnormal serum uric acid levels and abnormal left atrial diameter. Conclusion Left atrial enlargement and high uric acid levels increase the risk of left atrial thrombus or dense spontaneous echo contrast in atrial fibrillation patients with low to moderate CHA2DS2-VASc scores.